Magnetron-Sputtered, Biodegradable FeMn Foils: The Influence of Manganese Content on Microstructure, Mechanical, Corrosion, and Magnetic Properties - Jurgeleit, Till (Materials (Basel), 2018)
FeMn alloys show a great potential for the use as a biodegradable material for medical vascular implants. To optimize the material properties, with respect to the intended application, new fabrication methods also have to be investigated. In this work different Fe–FeMn32 multilayer films were deposited by magnetron sputtering. The deposition was done on a substrate structured by UV lithography. This technique allows the fabrication of in-situ structured foils. In order to investigate the influence of the Mn content on the material properties foils with an overall Mn content of 5, 10, 15, and 17 wt % were fabricated. The freestanding foils were annealed post-deposition, in order to homogenize them and adjust the material properties. The material was characterized in terms of microstructure, corrosion, mechanical, and magnetic properties using X-ray diffraction, electron microscopy, electrochemical polarization, immersion tests, uniaxial tensile tests, and vibrating sample magnetometry. Due to the unique microstructure that can be achieved by the fabrication via magnetron sputtering, the annealed foils showed a high mechanical yield strength (686–926 MPa) and tensile strength (712–1147 MPa). Owing the stabilization of the non-ferromagnetic ε- and γ-phase, it was shown that even Mn concentrations of 15–17 wt % are sufficient to distinctly enhance the magnetic resonance imaging (MRI) compatibility of FeMn alloys.